DNA Origami Reorganizes upon Interaction with Graphite: Implications for High-Resolution DNA Directed Protein Patterning - Masudur Rahman (Nanomaterials, 2016)
Although there is a long history of the study of the interaction of DNA with carbon surfaces, limited information exists regarding the interaction of complex DNA-based nanostructures with the important material graphite, which is closely related to graphene. In view of the capacity of DNA to direct the assembly of proteins and optical and electronic nanoparticles, the potential for combining DNA-based materials with graphite, which is an ultra-flat, conductive carbon substrate, requires evaluation. A series of imaging studies utilizing Atomic Force Microscopy has been applied in order to provide a unified picture of this important interaction of structured DNA and graphite. For the test structure examined, we observe a rapid destabilization of the complex DNA origami structure, consistent with a strong interaction of single-stranded DNA with the carbon surface. This destabilizing interaction can be obscured by an intentional or unintentional primary intervening layer of single-stranded DNA. Because the interaction of origami with graphite is not completely dissociative, and because the frustrated, expanded structure is relatively stable over time in solution, it is demonstrated that organized structures of pairs of the model protein streptavidin can be produced on carbon surfaces using DNA origami as the directing material.